Ainard of Dives and the Ste-Catherine-du-Mont office for St Katherine of Alexandria: 'Inter praecipuos cantores scientia musicae artis'. Issue 1 (April 2021) - BLASINA, JAMES J.
ABSTRACT: Orderic Vitalis writes that Ainard, a monk of Ste-Catherine-du-Mont monastery, composed a historia for St Katherine of Alexandria for use at his institution, which possessed the saint's oil-secreting finger bones. Through a series of historiographical errors, throughout the twentieth century it came to be believed either that Ainard composed not a liturgical office, but a prose vita of the saint, or that the office he had composed was lost. This article presents a survey of the oldest extant offices for St Katherine, showing that the office widely disseminated in German-speaking lands can be traced to Normandy, and through palaeographical and codicological analysis of its earliest source, Paris, Bibliothèque nationale de France, nouv. acq. lat. 1083, to Ste-Catherine-du-Mont in the late eleventh century. The office contained in this manuscript juxtaposes newly composed proper chants for St Katherine with existing chants from a variety of liturgical sources that honoured established saints, and emphasises the power of St Katherine's relics. The contents and themes of the office suggest an agenda of legitimisation and cultic publicity on the part of its creator, which would be consistent with the aims of a monk of Ste-Catherine. If this manuscript is indeed from Ste-Catherine-du-Mont, it likely records the office that Ainard composed. This attribution is reinforced by a textual-melodic style and modal organisation that grounds it in a later style of chant composition, which Ainard – a south German by birth – would likely have been familiar with.